Adverse Events Among Young Adults Following a Third Dose of Measles-Mumps-Rubella Vaccine. (7th August 2020) - Marin, Mona; Fiebelkorn, Amy Parker; Bi, Daoling; Coleman, Laura A; Routh, Janell; Curns, Aaron T; McLean, Huong Q
Abstract: Background: A third measles-mumps-rubella vaccine (MMR) dose (MMR3) is recommended in the United States for persons at increased risk for mumps during outbreaks. MMR3 is also likely given to persons who might have received 2 doses of MMR but lack documentation. Since MMR3 safety data are limited, we describe adverse events in persons receiving MMR3 in a nonoutbreak setting. Methods: Young adults with 2 documented MMR doses were administered MMR3. From 2 weeks before until 4 weeks after MMR3 receipt, participants reported daily on 11 solicited, common symptoms potentially associated with MMR. Weekly rate differences in post- vs prevaccination (baseline) were evaluated by Poisson regression. Baseline rates were subtracted from postvaccination rates of significantly different symptoms to estimate the number and percentage of participants with excess risk for symptoms post-MMR3. Descriptive analyses were performed for 3 postvaccination injection-site symptoms. Results: The 662 participants were aged 18–28 years (median = 20 years); 56% were women. Headache, joint problems, diarrhea, and lymphadenopathy rates were significantly higher postvaccination vs baseline. We estimate that 119 participants (18%) reported more symptoms after MMR3 than prevaccination. By symptom, 13%, 10%, 8%, and 6% experienced increased symptoms of headache, joint problems, diarrhea, and lymphadenopathy, respectively, after MMR3. The median onset was Days 3–6 postvaccination; the median duration was 1–2 days. One healthcare visit for a potential vaccination-related symptom (urticaria) was reported. Injection-site symptoms were reported by 163 participants (25%); the median duration was 1–2 days. Conclusions: Reported systemic and local events were mild and transient. MMR3 is safe and tolerable among young adults. Abstract : Reported systemic and local reactogenic events after the third dose of measles-mumps-rubella vaccine (MMR3) were transient, mild, and did not interfere with daily activities. MMR3 is safe and tolerable among young adults.